The Seventeenth-Century Manuscript Biography of Nicolaus Lancicius SJ. Authorship Attribution to Edward Lock SJ and Some General Questions - Čiurinskas, Mintautas (Senoji Lietuvos literatūra, 2019)
The paper contains the analysis of the manuscript work ‘Vita et virtutes V. P. Nicolai Lancicii Societatis Jesu’. Its 85-page copy survived in a manuscript notebook of the mid-eighteenth century that belonged to the house of Jesuit tertianship (domus tertiae probationis) at St Raphael’s Church in Vilnius. Currently, it is kept at the Library of the Polish Academy of Sciences and the Polish Academy of Arts and Sciences in Cracow (Biblioteka Naukowa Polskiej Akademii Umiejętności i Polskiej Akademii Nauk w Krakowie, Ms. No. 1010). Written in the epistolary form, this work contains biographical material about Fr Nicolaus Lancicius (1574–1652) collected by an anonymous author. Its composition is so thought-out that it can be considered an independent biography of Lancicius that mostly reflects his life in the Jesuit province of Lithuania.This study aimed to identify the author of this work basing the research on (auto)biographical data, other facts, and hints to the circumstances of events contained in the manuscript text. Analysis of the information in the text provides considerable albeit fragmentary data on the author’s life and the environment in Lithuania. It is evident that he was a member of the Jesuit province of Lithuania. He mentions periods of his living in Vilnius, Nesvizh, and Braunsberg where he could keep close company with Fr Lancicius and know him, but he never reveals his own identity. Although he does not name some of the individuals described, in many cases he does not suppress the names, and thus one chapter of present investigation is devoted to more important persons he knew (members of the Society of Jesus). This makes it possible to imagine, at least to some extent, the circle of people with whom he closely interacted in the Province of Lithuania.Three biographical moments were selected for identification. The central fact is that in 1947–1648 the author underwent tertianship in Nesvizh under the guidance of Fr Lancicius along with Fr Kazimieras Vijūkas-Kojalavičius and Fr Bernardus Roth. Since the full list (fifteen people) of that year’s tertianship is known, checking the facts of life of the Jesuits from this list against other selected biographical facts in the source text led to unambiguous conclusions that Fr Edward Lock (c. 1618–1670) was the one matching them. This Irish Jesuit of the Province of Lithuania should be considered one of the earliest biographers of Lancicius. He wrote a biographical work based on the material, notes, and reminiscences he had collected and also exploiting Lancicius’s published and unpublished works. Addressing the intended reader (in all likelihood, the provincial superior of the Province of Lithuania) of his biographical letter, he expresses hope that some other writer will come up and will make use of his work creating, in a rhetorically embellished style, a comprehensive biography of Lancicius intended for printing.Fr Lock was active in the Province of Lithuania from 1639 to 1655. The article presents currently accessible information on his life and work before his death in Dublin, shortly upon his return to his homeland, Ireland. It should be noted that the autobiographical information contained in the work vividly illustrates and adds to the facts of his life known from encyclopaedic reference works.Although intended for public use, for those interested in Lancicius’ personality, Fr Lock’s work on Fr Lancicius’ life remained a manuscript. The extant copy of the first half of the eighteenth century shows that it might not have been unknown, but so far no traces of the existence or use of the manuscript have been known. None of Jesuit historians – Rostowski or the bibliographers of the Society of Jesus – mention this work on Lancicius or Lock himself among the Jesuits distinguished by their literary activities.The analysis of the manuscript provides new information not only on Lancicius but also on literary activities of the province’s Jesuits, while the identification of the author will enable a better understanding of the purpose, sources, the structure, the content, the writing method of this biographical work and other issues in future analysis.Fr Lock’s name expands the list of foreign Jesuits who left a trace in the writings of Lithuania. He was also one of the few seventeenth-century Jesuits whose life points to the contacts between the Jesuit Province of Lithuania and Ireland.
Keywords: Mikalojus Lancicijus; Nicolaus Lancicius; Mikołaj Lęczycki; biography; Lithuanian Jesuit Province; Latin literature of the Grand Duchy of Lithuania of the seventeenth century; Irish Jesuits; Eduardas Lockas; Eduardus Lock; Edward Lock; manuscript heritage